Alcohol misuse and injury outcomes in young people: a cohort analysis of linked primary and secondary data in England. (November 2016) - Lester, Louise; Baker, Ruth; Orton, Elizabeth
Abstract: Background: The burden of disease attributed to alcohol consumption is a global problem. Alcohol misuse is thought to be a risk factor for injury in young people, though few studies have described this association in detail. This study aimed to assess the risk of hospital admission for injury in young people with a history of alcohol misuse. Methods: We conducted a cohort study of young people aged 10–24 years registered at a Clinical Practice Research Datalink general practice between Jan 1, 1998, and Dec 31, 2013, with linked Hospital Episode Statistics data. Exposed individuals had an alcohol-specific admission to hospital between the ages of 10 and 24 years, as defined by the International Classification of Diseases, 10th revision. Unexposed individuals had no alcohol-specific admission, and were frequency matched by age (plus or minus 5 years) and general practice (ratio 10 to 1). The incidence rate (events per person-year) of first injury-related admission to hospital was calculated and the mechanisms described. Hazard ratios (HR) adjusted for age, sex, deprivation, and region were estimated by Cox regression, with an interaction term included between exposure and time. Findings: The cohort comprised 11 042 exposed and 110 656 unexposed individuals. Exposed individuals had longer median follow-up time than unexposed individuals (2·17 years [IQR 0·82–4·44] vs 1·20 [0·38–3·09]), and were more likely to be from the most deprived socioeconomic quintile (3274 [29·7%] exposed vs 26 990 [24·3%] unexposed) and be male (56·8% exposed vs 47·3% unexposed). 4944 injury-related admissions occurred (2092 exposed, 2852 unexposed), with injury rates higher in those with than in those without a previous alcohol admission (73·92 per 1000 person-years, 95% CI 70·82–77·16 vs 12·36, 11·91–12·81). Individuals with a previous alcohol-specific admission were 5·28 times more likely to have an injury admission than those without at 1 year (HR 5·28, 95% CI 4·97–5·60), with the interaction term (0·65, 95% CI 0·62–0·67) indicating that injury risk significantly depreciated after alcohol admission. The most common injury mechanism was poisoning in exposed individuals and falls in unexposed individuals. Interpretation: This is the largest study, to our knowledge, demonstrating that alcohol-specific admissions to hospital are associated with subsequent admission for injury in young people, with risk of injury greatest after the alcohol admission and reducing over time. This finding indicates a need for early intervention during admissions and after discharge, providing information and referral (eg, specialist alcohol or mental health services), and developing effective interventions to reduce subsequent risk of injury. Funding: National Institute for Health Research (NIHR) School for Primary Care Research.